Combat stiffness of the launcher platform - Lazarević, Miloš S. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Possible loads on a multiple rocket launcher have been systemized and analyzed. Based on the analysis of loads, a mathematical-mechanical model has been  made to describe the stability of a MLR hit by a high explosive-fragmentation projectile (HE-FRAG) in a close range. The results give the dependency of the launcher stability on explosion proximity, its typeand the explosive charge mass. The stability limit is determined by the force that can turn over the laucher and compromise the stability of projectiles inside. To simplify the given model, the kinetic energy is calculated for a projectile fragment that hits the launcher.
Keywords: load; explosion effect; surface explosion; above ground explosion; conditions; critical pressure; critical distance; overturn; stability; kinetic energy